Arsenolite: a quasi-hydrostatic solid pressure-transmitting medium. (16th September 2016) - Sans, J A; Manjón, F J; Popescu, C; Muñoz, A; Rodríguez-Hernández, P; Jordá, J L; Rey, F
Abstract: This study reports the experimental characterization of the hydrostatic properties of arsenolite (As4 O6 ), a molecular solid which is one of the softest minerals in the absence of hydrogen bonding. The high compressibility of arsenolite and its stability up to 15 GPa have been proved by x-ray diffraction measurements, and the progressive loss of hydrostaticity with increasing pressure up to 20 GPa has been monitored by ruby photoluminescence. Arsenolite has been found to exhibit hydrostatic behavior up to 2.5 GPa and a quasi-hydrostatic behavior up to 10 GPa at room temperature. This result opens the way to explore other molecular solids as possible quasi-hydrostatic pressure-transmitting media. The validity of arsenolite as an insulating, stable, non-penetrating and quasi-hydrostatic medium is explored by the study of the x-ray diffraction of zeolite ITQ-29 at high pressure.